The effect of diesel exhaust emission on blood brain barrier integrity and function - Heidari Nejad, Sayeh (Curtin University, 2014)
Epidemiological studies indicate that exposure to diesel exhaust (DE) is associated with vascular-based disorders. An in vivo murine model was utilized to determine the effect of DE inhalation on neurovascular integrity. The study demonstrated that exposure to DE compromises the integrity and function of cerebral capillary vessels. Heightened neurovascular inflammation as a consequence of sub-chronic DE exposure may contribute to risk for neurovascular-based disorders.